2021
DOI: 10.3389/fonc.2021.679634
|View full text |Cite
|
Sign up to set email alerts
|

m(6)A Modification of lncRNA NEAT1 Regulates Chronic Myelocytic Leukemia Progression via miR-766-5p/CDKN1A Axis

Abstract: BackgroundChronic myeloid leukemia (CML) is an acquired hematopoietic stem malignant disease originating from the myeloid system. Long non-coding RNAs (lncRNAs) have been widely explored in cancer tumorigenesis. However, their roles in CML remain largely unclear.MethodsThe peripheral blood mononuclear cells (PBMCs) and CML cell lines (K562, KCL22, MEG01, BV173) were collected for in vitro research. Real-time quantitative polymerase chain reaction was used to determine the mRNA expression levels. Cell viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…The result was consistent with other studies [12]. For instance, m6A modification of lncRNA NEAT1 inhibited cell viability and promoted the apoptosis of CML cells [22].…”
Section: Discussionsupporting
confidence: 93%
“…The result was consistent with other studies [12]. For instance, m6A modification of lncRNA NEAT1 inhibited cell viability and promoted the apoptosis of CML cells [22].…”
Section: Discussionsupporting
confidence: 93%
“…Fang-Yi Yao et al. reported that METTL3 was downregulated in CML cells, resulting in a decrease in the protein level of nuclear enriched abundant transcript 1 ( NEAT1 ) ( 70 ). Furthermore, METTL3 downregulation in CMLs reduced its ability to modify NETA1 m 6 A, subsequently enhancing CML cell viability and inhibiting CML cell apoptosis.…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
“…Higher expression of METTL3 in AML is critical to maintain the undifferentiation of AML cells, promote the growth of AML cells, and inhibit AML cell apoptosis ( 31 , 32 , 66 ). In CML, TKI resistance always makes it more difficult to cure patients with CML, while METTL3 has been found to affect the apoptosis, proliferation, and viability of CML cells with higher expression ( 60 , 61 , 68 , 70 ). More importantly, METTL3 depletion notably damages the proliferation of primary CML cells and TKI-resistant CML cells, which suggests that METTL3 inhibitors may have novel potential to cure TKI-resistant CML patients.…”
Section: The Potential Application In Cancer Therapymentioning
confidence: 99%
“…Therefore, the findings suggest that METTL3 is a novel oncogene in the pathogenesis of CML and a potential therapeutic target for TKIs-resistant CML. Another recent finding [ 131 ] also revealed that via modulating the miR-766-5p/CDKN1A axis, METTL3 could modify long non-coding RNAs (lncRNAs) nuclear-enriched transcript 1 (NEAT1), thus controlling the progressive process of CML disorder and playing an oncogenic role in CML. NEAT1 is currently known to have low expression levels in CML cell lines or PBMCs of CML patients [ 131 ].…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%
“…Another recent finding [ 131 ] also revealed that via modulating the miR-766-5p/CDKN1A axis, METTL3 could modify long non-coding RNAs (lncRNAs) nuclear-enriched transcript 1 (NEAT1), thus controlling the progressive process of CML disorder and playing an oncogenic role in CML. NEAT1 is currently known to have low expression levels in CML cell lines or PBMCs of CML patients [ 131 ]. Mechanistically, the dysfunction of m 6 A methyltransferase METTL3 causes the abnormal expression of NEAT1 in CML, and the overexpression of NEAT1 greatly promotes the death of CML cells.…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%